The Effect of Cardiovascular Medications on Disease-Related Outcomes in Idiopathic Pulmonary Fibrosis: A Systematic Review and Meta-Analysis - Zhang, Wan-Tong; Wang, Xu-Jie; Xue, Chun-Miao; Ji, Xin-Yu; Pan, Lin; Weng, Wei-Liang; Li, Qiu-Yan; Hua, Guo-Dong; Zhu, Bao-Chen (Frontiers in Pharmacology, 2021)
Background: Multiple studies have revealed Idiopathic pulmonary fibrosis (IPF) patients are more at risk for cardiovascular diseases and many IPF patients receive cardiovascular medications like statins, ACEI, ARB and anticoagulants. Existing studies have reported divergent findings on the link between cardiovascular medications and fibrotic disease processes. The aim of this study is to synthesise the evidence on the efficacy of cardiovascular medications in IPF. Methods: We searched studies reporting the effect of cardiovascular medications on IPF in the PubMed, Embase, Web of Science, Cochrane Library, and two Chinese databases (China National Knowledge Internet database and China Wanfang database). We calculated survival data, FVC decline and IPF-related mortality to assess the efficacy of cardiovascular medications in IPF. We also estimated statistical heterogeneity by using I2 and Cochran Q tests and publication bias was evaluated by risk of bias tools ROBINS-I. Results：A total of 12 studies were included in the analysis. The included studies had moderate-to-serious risk of bias. Statin use was associated with a reduction in mortality (HR, 0.89; 95% CI 0.83-0.97). Meta-analysis did not demonstrate any significant relationship between statin use and the FVC decline. (HR, 0.86; 95% CI 0.73-1.02), ACEI/ARB use and survival data. (HR, 0.92; 95% CI 0.73-1.15) as well as anticoagulants use and survival data. (HR, 1.16; 95% CI 0.62-2.19). Conclusion: Our study suggested that a consistent relationship between statin therapy and survival data in IPF population. However, there is currently insufficient evidence to conclude the effect of ACEI, ARB and anticoagulant therapy on IPF population especially to the disease-related outcomes in IPF.